PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN FARMASI YANG TERDAFTAR: Studi Empiris pada BURSA EFEK INDONESIA - I Dewa Gede Andi Pratama; Ni Made Christin Dwitrayani; Ni Made Ernila Junipisa (Journal Research of Accounting, 2023)
The share price is the price of a share when the market is in progress or when the market is closed and can change at any time depending on the demand and supply of these shares. This study aims to determine the effect of financial ratios on stock prices in pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) in 2017-2021, either partially or simultaneously. This study uses financial ratios, namely Current Ratio, Debt to Equity Ratio, Return On Equity, and Earning Per Share which are used as Independent Variables and Stock Prices as the Dependent Variable. The population in this study are pharmaceutical companies listed on the Indonesia Stock Exchange (IDX). The research sample consisted of 14 pharmaceutical companies that met the criteria using a purposive sampling method. The data used in this study is secondary data in the form of pharmaceutical company financial reports for 2017-2021. The data collection technique used is documentation. The data analysis technique used is multiple linear regression. The results of the study show that Cuurent Ratio, Return On Equity, Earning Per Share have a positive effect on stock prices while the Debt To Equity Ratio has a negative effect on stock prices.